The history of double taxation conventions in the pre-BEPS era - Lang, Michael; Reimer, Ekkehart (European and international tax law and policy series, 2020)
This book analyses the evolution of tax treaties practices from the early days of the history of international taxation until the beginning of the BEPS era.